PENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL EXAMPLES NON EXAMPLES PADA MATA PELAJARAN IPA DI KELAS IV SD NEGERI 040455 BERASTAGI - Irma Sari Br Purba (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2019)
This study was conducted to determine the improvement of fourth grade science learning outcomes using the examples non examples learning model. The subjects were all students in fourth grade 040455 Berastagi, Karo. The object of the research is the improvement of the fourth grade science learning outcomes using the examples non examples learning model. The research instrument used was the observation sheet and tests. From the analysis of the data obtained from observations the implementation of learning activities of teachers increased 19,7% from a value of 60% to 79.7%, student activity increased from a score of 68% to 86%, the completeness of individuals who expressed achieving KKM scores of 70, classical completeness increased from 70% to 86.67%, and the average value increased from 67,33 to 70,33. Keywords: learning result of sciences, examples non examples